AN ANALYSIS OF MORAL AND EDUCATIONAL VALUES ON MADURA FOLK SONGS - Abdul Wakil (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2015)
At this moment traditional songs was not pay attention so that almost the traditional song is not well known by young generations. The position of traditional songs was lost with technology. If there is not an conservation and appreciation for traditional songs especially Madura traditional songs, so the traditional song can be lost in the future so that writer try to analysis of moral and educational values on Madura folk songs. The discussion in this thesis the author tried to review the pedagogical values particularly with regard to the morality contained in the lyrics of Madura folk song. The author only took eight songs contained in a book of poetry titled Madura folk songs